2018
DOI: 10.18632/oncotarget.26385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pre-mir-34a rs72631823 single nucleotide polymorphism in triple negative breast cancer: A case-control study

Abstract: AimThe purpose of this study is to evaluate the role of pre-miR34a rs72631823 as potential risk factor and/or prognostic marker in patients with triple negative breast cancer.Methods114 samples of DNA from paraffin embedded breast normal tissues of patients with triple negative breast cancer and 124 samples of healthy controls were collected and analyzed for pre-miR34a rs72631823 polymorphism.ResultsPre-miR34a rs72631823 A allele was associated with increased TNBC risk both in univariate and multivariate analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…conversely, mirnas such as mir-155 are reportedly overexpressed in various types of cancer, and act as oncogenes (44). changes in mirna expression contribute to the initiation and progression of cancer (45,46). The association between mirnas and tumors suggests that mirnas may be altered in patients with gastric cancer (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…conversely, mirnas such as mir-155 are reportedly overexpressed in various types of cancer, and act as oncogenes (44). changes in mirna expression contribute to the initiation and progression of cancer (45,46). The association between mirnas and tumors suggests that mirnas may be altered in patients with gastric cancer (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…The full texts of the remaining 79 records were evaluated and 10 articles were excluded for the following reasons: insufficient reported data ( n : 4) [16,17,18,19], studying other genes or polymorphisms ( n : 3) [20,21,22], not a case-control design ( n : 2) [23,24], and a duplicate study ( n : 1) [25]. Finally, a total of 69 articles remained [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85<...>…”
Section: Resultsmentioning
confidence: 99%
“…It's worth noting that although this limitation above, an essential element of the validity of our study is its agreement with HWE in both study groups, particularly the controls which exclude any genotyping errors or guided sample selection by the authors. Another raised limitation in this study could be related to evaluation of the study variant in FFPE normal colon tissue samples, which, however, is "a very common source for DNA extraction in the studies regarding microRNAs" 47 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miRNA SNPs might also cause an aberrant function of the miRNA in regulating the putative target genes 44 . Previous researches have shown that MIR34A variants could modulate the susceptibility of individuals to multiple human cancers, including osteosarcoma 45 , colon cancer 46 , and breast cancer 47 . The present results revealed that MIR34A rs2666433 AA and AG genotype carriers were 5.7 and 2.8 more likely to develop cancer than GG carriers.…”
Section: Discussionmentioning
confidence: 99%